İmam Hatip Lisesi Meslek dersleri öğretmenlerinin Kur'an-ı Kerim derslerinde öğrencilerin derse katılımını sağlama yolları - Özdemir, Şuayip; Karateke, Tuncay (My University, 2019)
Bu araştırma, İmam-Hatip Lisesi meslek dersleri öğretmenlerinin Kur’an-ı Kerim derslerinde öğrencilerin derse katılımını sağlama yollarını belirlemeyi amaçlayan, nitel yöntemin durum deseninin kullanıldığı bir araştırmadır. Araştırmanın çalış- ma grubunu, amaçlı örneklem yöntemlerinden ölçüt örnekleme yoluyla seçilen 23 İmam-Hatip Lisesi meslek dersi öğretmeni oluşturmaktadır. Veriler, yarı yapılan- dırılmış görüşme formu ile toplanmış ve içerik analizi tekniği ile çözümlenmiştir. Araştırma sonucunda öğretmenlerin öğrencileri derse katma yolları konusundaki görüşlerinin dersin içeriğine göre farklılık gösterdiği tespit edilmiştir. Öğretmen- lerin öğrencilerin derse katılımını sağlama yollarından ön plana çıkanlar; okuma seviyesi iyi olan öğrenciden başlayarak rastlantısal olarak derse katma, çalışan/gö- nüllü öğrencilere öncelik vererek derse katma, toplu olarak derse katma, rastlantısal olarak derse katma şeklindedir. Öğretmenlerin, ezber metinlerini yüzünden oku- ma derslerinde, okuma seviyesi iyi olan öğrencilerden başlayarak rastlantısal derse katma; ezber metinlerini dinleme derslerinde, “çalışan/gönüllü öğrencilere öncelik vererek derse katma”; yüzünden okuma derslerinde, “okuma seviyesi iyi olan öğ- rencilerden başlayarak rastlantısal derse katma ve “rastlantısal olarak derse katma”; elif-ba derslerinde “öğrencileri toplu olarak derse katma” yollarını daha fazla kul- landıkları belirlenmiştir.This study is a research aims to determine methods of providing students class at- tendance by vocational teachers in the Holy Quran classes in Imam Hatip High Schools, using the situational pattern of qualitative methods. The sampling group of the research consists of 23 Imam-Hatip High School vocational teachers selected through criterion sampling method from among purposive sampling methods. The data were collected through semi-structured interviews and analyzed with content analysis technique. As a result of the research, it was determined that the opinions of the teachers about the ways of encouraging the students to attend the lesson dif- fered according to the content of the lesson. It was determined that the views of the teachers on the ways of adding students to the lesson differed according to the content of the lesson. Some of the methods used by the teachers in order to have the students participate in lessons are as follows: Randomly providing the atten- dance starting from the students whose reading level is of the best, providing the attendance by giving priority to the students who study/are voluntary, providing the collective attendance by students to the lesson, randomly providing the attendance by students to the lesson. It was determined that the teachers used randomly provid- ing the attendance starting from the students whose reading level is of the best in reading lessons of memorized texts of Quran; “providing the attendance by giving priority to the students who study/are voluntary in listening lessons of memorised text of Quran; randomly providing the attendance starting from the students whose reading level is of the best and randomly providing the attendance by students to the lesson in Quran reading lessons; providing the collective attendance by students to the lesson in alif-ba lessons way more.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Din eğitimi; İmam Hatip Lisesi Kur'an-ı Kerim dersi; İmam Hatip Lisesi Meslek dersi öğretmeni; Derse katılım